2011
DOI: 10.1049/mnl.2011.0195
|View full text |Cite
|
Sign up to set email alerts
|

Tunable bandgap opening in the proposed structure of silicon-doped graphene

Abstract: Abstract-A specific structure of doped graphene with substituted silicon impurity is introduced and ab. initio density-functional approach is applied for energy band structure calculation of proposed structure. Using the band structure calculation for different silicon sites in the host graphene, the effect of silicon concentration and unit cell geometry on the bandgap of the proposed structure is also investigated. Chemically silicon doped graphene results in an energy gap as large as 2eV according to DFT cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 31 publications
5
22
0
Order By: Relevance
“…Impurity concentrations of 3 % reduce the conductivity to less than one-tenth of the pure graphene conductivity. These results suggest that silicon impurity is more effective at reducing the conductivity than the isotopic dopant; experiments have shown that the thermal conductivity of graphene isotopically enriched with 1.1 % of 13 C is reduced to 63 % of pure graphene [18]. Further, our results suggest that silicon impurity is superior to nitrogen doping, which has been observed to reduce the thermal conductivity to 30 % of pure graphene at of 3 % nitrogen impurity [16].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Impurity concentrations of 3 % reduce the conductivity to less than one-tenth of the pure graphene conductivity. These results suggest that silicon impurity is more effective at reducing the conductivity than the isotopic dopant; experiments have shown that the thermal conductivity of graphene isotopically enriched with 1.1 % of 13 C is reduced to 63 % of pure graphene [18]. Further, our results suggest that silicon impurity is superior to nitrogen doping, which has been observed to reduce the thermal conductivity to 30 % of pure graphene at of 3 % nitrogen impurity [16].…”
Section: Discussionsupporting
confidence: 55%
“…However, for practical applications, the zero bandgap of pristine graphene must be addressed with proper functionalization. The insertion of impurity or dopant atoms is the most effective method for addressing the bandgap concerns [10,13]. On the other hand, it can negatively impact thermal conduction properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the bandgap of N-functionalized graphene is almost 1.23 eV 85 and the nature of semiconductor is of n-type. However, maximum opening of bandgap can occur up to 2.01 eV depending upon the percentage of Si in graphene 86 and the structure is popularly known as siliphene.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…adsorption of hydrogen molecule [54], doping with silicon [55] and group IV element [56], adsorption of water molecule [57], and aromatic molecules [58]. In experiment, it has been demonstrated that a bandgap starting from 2.5 meV up to 450 meV can be introduced in…”
Section: Introductionmentioning
confidence: 99%